Distribution of races and Tox genes in Pyrenophora tritici-repentis isolates from wheat in Argentina - Moreno, María Virginia (2015)
Tan spot, caused by Pyrenophora tritici-repentis, is a common disease in wheat-growing regions of Argentina. In this study 65 isolates of P. tritici-repentis obtained from different cultivars and wheat regions of Argentina were assessed for their virulence on six wheat cultivars/lines (Glenlea, Salomouni, Katepwa, M-3, 6B365 and 6B662) and for the presence/absence of the Tox genes based on a PCR approach. Thirty-six isolates were assigned to races, of which races 4 and 8 were dominant. Results for molecular analysis of ToxA, ToxB, ToxB-like and toxb genes showed that 57 isolates possessed the ToxA gene whereas only one isolate possessed ToxA and ToxB genes. There was no correlation between races and the toxin genotypes. It is suggested that P. tritici-repentis exhibits a complex race structure in Argentina.